Placental mesenchymal dysplasia - Huertas, Erasmo (2008)
Placental mesenchymal dysplasia is a rare condition of placentomegaly and abnormal chorionic villous, often clinically confused as partial hydatidiform mole. However, it is different clinically and pathologically, with high incidence of intrauterine growth restriction and stillbirth. We present the clinical course of a pregnant woman carrying placental mesenchymal dysplasia, the first case diagnosed at the Maternal Perinatal National Institute, how to suspect diagnosis and gestational care. There was need for caesarean section at 27 weeks gestation, obtaining a 1 048 g newborn girl, with Apgar 8 at the first minute and 9 at the fifth minute, bloody amniotic fluid in regular quantity and placentomegaly. Patient evolved satisfactorily and was discharged on the third hospitalization day. An abdominal liver tumor was confirmed in the newborn and surgical pathology report was liver mesenchymal hamartoma.